UPAYA PENINGKATAN DAYA SAING PRODUK OLAHAN PUCUK DAUN TEH RAKYAT DI KECAMATAN BOJONG KABUPATEN PURWAKARTA - Rani Andriani Budi Kusumo; Anne Charin; Gema Wibawa Mukti (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2017)
Acreage and production of tea plant in Purwakarta decreased compared to previous years. Price of tea leaf is less favorable making farmers less eager to continue to pursue this commodity. Sindangpanon farmer group seeks to increase the value added tea leaf to process into dry tea, but various obstacles make this business has not developed. The purpose of this study was to: 1) analyze the problems faced by farmers' groups in running the business processing tea leaf; 2) analyze the impact of efforts to increase the capacity of farmer groups to produce competitive products. This study is an action research and designed with a qualitative design. Informants in this study is the management and members of farmer groups Sindangpanon well as the staff of the Department of Agriculture, Plantation and forestry, PurwakartaDistrict. Data were analyzed with descriptive analysis. The results showed the tea leaf processing enterprises difficult to develop due to lack of competitive products, the market is still limited and the managerial ability needs to be improved. Event strengthening the capacity of farmer groups that do have an impact on increasing the knowledge and skills of the group members in running the business and increased sales volume.